If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + y + 6 = 86 Reorder the terms: 6 + x + y = 86 Solving 6 + x + y = 86 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + x + -6 + y = 86 + -6 Reorder the terms: 6 + -6 + x + y = 86 + -6 Combine like terms: 6 + -6 = 0 0 + x + y = 86 + -6 x + y = 86 + -6 Combine like terms: 86 + -6 = 80 x + y = 80 Add '-1y' to each side of the equation. x + y + -1y = 80 + -1y Combine like terms: y + -1y = 0 x + 0 = 80 + -1y x = 80 + -1y Simplifying x = 80 + -1y
| 18x+30-9=18x+21 | | 2x+66=102 | | 150=20-6x | | 5x-(4x+4)=2x-35 | | n+54=3n | | 6x+1=(-11) | | 13000.00+25000.00x=27500.00 | | 1/2/5/8 | | (2x+6)/5=(3x)/9 | | 2(x+4)+22=-4x | | 3/10+5/12 | | -2x-4x=0 | | 54n/12n+6 | | 4(6x-8)=8x | | 210+.25x=357.5 | | 4x+2m=6 | | 13(x-3)=7x+3 | | 5x+1000y=0 | | 55=2x+5x-8 | | 7x+4+15x-5=8x+4+9 | | 2g+5=4g+3 | | x+.05395x=500 | | 0=-4.9(t^2-9)+47 | | (1/4)^4 | | S+0.04s=105.04 | | -4-7=3x+6-2x | | 5/3(x+3)=1 | | -19=3x+x-3 | | n^2+28n+c= | | 4x+28=-5x | | 9x+x^2=8x+20 | | 3x^2+9x= |